Kajian Kelayakan Adaptive Reuse pada Bangunan Tua di Koridor Jalan Kesawan Kota Medan - Rani, Nandi; Ruliansyah, Farhan Putra; Nuraini, Cut Nuraini; Andriana, Melly (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The Kesawan Corridor in Medan City is a historic district lined with colonial-era buildings of high architectural and historical value. However, many of these structures have experienced physical deterioration and functional obsolescence due to changing urban dynamics and lack of proper conservation. This research aims to assess the feasibility of adaptive reuse as a sustainable preservation strategy for historic buildings in this area. A qualitative case study approach was employed, including visual observation, in-depth interviews, and literature review. The potential buildings examined include the AVROS Building, London Sumatra Building, the Old Bank Indonesia, the former Warenhuis, and Tjong A Fie Mansion as a benchmark of successful conservation. The findings reveal that most of these buildings have high potential for new uses—commercial, educational, or cultural—if approached with context-sensitive and historically respectful strategies. Adaptive reuse presents a viable path for urban heritage revitalization in Medan